Productivity in the euro area: any evidence of convergence? - David Sondermann (European Central Bank (ECB), 2012)
Sizable prevailing real economic disparities among countries in a currency union potentially involve costs for those countries for which the aggregate policy stance is not appropriate. This paper contributes to the literature by testing for productivity convergence among euro area countries. While no convergence can be found on the aggregate level, selected service sectors and manufacturing sub-industries indicate evidence of convergence. In a search for factors influencing productivity, investments in research and development as well as a high skill level of employees are shown to be beneficial whereas regulations constitute a burden. Consequently, euro area countries should engage in structural reforms where necessary to provide a more competitive environment, eventually facilitating economic convergence.
Keywords: C33; O47; J24; L60; L80; 330; convergence; manufacturing and service sector; panel unit root test; productivity